Floral Diversity and Vegetation Ecology of the Pathiramanal Island in Vembanad Lake, Kerala - Balasubramanian, P.; Azeez, P. A. (Indian Forester, 2012)
This paper highlights the floristic richness and vegetation association in the Pathiramanal Island, an important mangrove location in Kerala, South-western coast. Ceriops tagal, Excoecaria agallocha and Cerbera odollam constituted the dominant mangroves in Pathiramanal Island. The need for conservation of this area is emphasized.